2021
DOI: 10.1371/journal.pone.0259697
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a social support family caregiver training program on changing blood pressure and lipid levels among elderly at risk of hypertension in a northern Thai community

Abstract: Hypertension is becoming increasingly prevalent among the elderly. Family caregivers play an important role in caring for elderly people and empowering them to care for themselves. This study’s goal was to see how social support training for family caregivers affected changes in hypertension, total cholesterol, and high-density lipoprotein (HDL), and how such support led to the prevention of hypertension behaviors among the elderly in rural areas. This was a quasi-experimental study with 268 elderly people at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
(29 reference statements)
0
3
0
1
Order By: Relevance
“…Dukungan sosial dapat diberikan dari lingkungan sekitar seperti keluarga, tetangga, kader, petugas kesehatan dan pemerintah. Dukungan dan sikap dari lingkungan terdekat, yaitu keluarga dan masyarakat di sekitarnya, akan berpengaruh kepada penerimaan terhadap penyakit yang diidap, keberlanjutan terapi, stressor psikologis dan keberhasilan pengobatan (Boonyathee et al, 2021;Higa et al, 2021;Pesantes et al, 2018). Edukasi yang melibatkan keluarga diharapkan akan meningkatkan dukungan keluarga.…”
Section: Hasil Dan Pembahasanunclassified
“…Dukungan sosial dapat diberikan dari lingkungan sekitar seperti keluarga, tetangga, kader, petugas kesehatan dan pemerintah. Dukungan dan sikap dari lingkungan terdekat, yaitu keluarga dan masyarakat di sekitarnya, akan berpengaruh kepada penerimaan terhadap penyakit yang diidap, keberlanjutan terapi, stressor psikologis dan keberhasilan pengobatan (Boonyathee et al, 2021;Higa et al, 2021;Pesantes et al, 2018). Edukasi yang melibatkan keluarga diharapkan akan meningkatkan dukungan keluarga.…”
Section: Hasil Dan Pembahasanunclassified
“…10 However, hypertension among older adults living in Thai communities can be prevented by self-care behaviors (SCB). 13 Health literacy (HL) is the ability to obtain the knowledge, skills, and confidence to take action toward health and understand necessary health information and services to make appropriate health decisions. 14,15 Individuals with higher education levels or socioeconomic status can have low HL if they struggle to understand and apply health information effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Research exists to demonstrate that antihypertension medications reduce the risk for hospitalization among the general population, 7 - 10 and people with IDD rely on caregivers to help them with medication refills and management. 23 Also, it has been shown that health interventions which include traditional caregivers have been successful in improving the health of people without IDD; 24 - 26 but randomized controlled trials (RCTs) have not been conducted to test the efficacy of targeting both adults with IDD and their self-identified helpers to reduce hospital use.…”
Section: Introductionmentioning
confidence: 99%